Composición de la avifauna en un gradiente altitudinal del matorral seco del valle de Catamayo - Apolo Chamba, Maria Antonella (2018)
Abstract:The present work was oriented to define the bird composition of Alamala, sector that houses an important remnant of dry scrubland in the Catamayo Valley. The richness and diversity of birds were evaluated in two periods (October / 2017 and January-February / 2018) through counting points, to achieve visual and auditory bird records. A total of 27 species were recorded during the sampling. The site presented high diversity according to the Simpson index (0.90) and average diversity with the Shannon index (2.68). Of the total of registered species, 33% correspond to endemic species of the Tumbesian Lowlands and 7% of the highland of Southwestern Region; respect sensitivity, 70% of the registered species have low environmental sensitivity. The diversity of birds in the study sector is influenced by the seasonality of the site, increases in rainy seasons and decreases in dry seasons, which shows a direct response from the community of birds in the sector to the availability of resources.